Focusing a Gaussian beam in nanostructured non-periodic GRIN microlenses - Nowosielski, Jedrzej M.; Buczynski, Ryszard; Hudelist, Florian; Waddie, Andrew; Pysz, Dariusz; Stępień, Ryszard; Kujawa, Ireneusz; Taghizadeh, Mohammad R. (Photonics Letters of Poland, 2010)
Modeling the propagation of a Gaussian beam in a nanostructured gradient index microlens is reported. The nanostructured GRIN microlens is composed of subwavelength discrete dielectric rods. We compare the performance of nanostructured gradient index microlenses against conventional GRIN microlenses for Gaussian beam focusing. The 3D FDTD method is used for numerical analysis of optical systems. Full Text: PDF References: W. J. Tomlinson, "Application of GRIN rod lenses in optical fiber communication systems," Appl. Opt. 19, 1127-1138 (1980). [CrossRef] S. Sinzinger, and J. Jahns, Microoptics Wiley-VCH, Weinheim, 2003. F. Hudelist, R. Buczynski, A. J. Waddie, and M. R. Taghizadeh, "Design and fabrication of nano-structured gradient index microlenses," Opt. Express 17, 3255-3263 (2009). [CrossRef] F. Hudelist, J. M. Nowosielski, R. Buczynski, A. J. Waddie, and M. R. Taghizadeh, "Nanostructured elliptical gradient-index microlenses," Opt. Lett. 35, 130-132 (2010). [CrossRef] C. Gomez-Reino, M. V. Perez, and C. Bao, Gradient-Index Optics: Fundamentals and Applications Springer, Berlin, 2002 A. Farjadpour, D. Roundy, A. Rodriguez, M. Ibanescu, P. Bermel, J. D. Joannopoulos, S. G. Johnson, and G. Burr, "Improving accuracy by subpixel smoothing in FDTD," Opt. Lett. 31 (20), 297 (2006). [CrossRef]